BLOCKADE OF THE APPELLATE BODY AND MULTI-PARTY INTERIM APPEAL ARBITRATION ARRANGEMENT (MPIA) - Zdravkovic, Uros; Krnjaić, Magdalena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The World Trade Organization (WTO) dispute settlement system is organized in two stages. In the first instance, the existing dispute between the members is resolved by ad hoc panels, and if the parties are not satisfied with the panel's reports, the dispute is finally resolved by the second instance body, the Appellate Body (AB).Since 2017, the United States has repeatedly blocked the appointment of members of the Appellate Body, which has caused a progressive reduction in the number of members. As the mandate of two of the three remaining members ended on December 10, 2019, the highest institution in the WTO dispute resolution system has therefore become de facto dysfunctional. The blockade of the Appellate Body has resulted in a crisis in the WTO dispute settlement mechanism, which ultimately leads to the dispute not being definitively resolved.In order to remove the blockade of the Appellate Body and its consequences, some WTO members have established a complaint redress mechanism in accordance with Article 25 of the Agreement on Dispute Resolution Rules and Procedures (DSU). The mentioned Article 25 envisages the possibility of establishing arbitration for resolving disputes at the multilateral level. This provision serves as a basis for establishing an arbitration mechanism that would act as an alternative to the Appellate Body while it is under blockade. In 2020, on April 30, after intensive debates on how to implement this idea, the Multi-party Interim Appeal Arrangement (MPIA) came into force. The arrangement offers a short-term solution to overcome the problem of blocking the Appellate Body, while members try to find a more permanent solution.This article examines the role that the newly established MPIA would play in the future of the WTO, as well as the procedural innovations it has introduced, which can serve as a trigger for systematic changes in resolving disputes in front of the WTO.
Keywords: WTO; blockade of the Appellate Body; arbitration; MPIA arrangement